2017
DOI: 10.1016/j.jaip.2016.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Idiopathic Urticaria: Systemic Complaints and Their Relationship with Disease and Immune Measures

Abstract: Despite similar demographic characteristics and basophil profiles as patients with CIU-NSC, patients with CIU-SC have features of greater disease burden (work absences, emergency department visits, and corticosteroid use), quality-of-life impairment, and baseline serum tryptase levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 17 publications
3
29
0
Order By: Relevance
“…A recent study reported a high frequency of systemic signs and symptoms such as joint pain or swelling (55.3%), headache/fatigue (47.6%), flushing (42.7%), wheezing or breathlessness (30.1%), gastrointestinal complaints (26.2%), and palpitations (9.7%) in two thirds of adult patients with CSU that are probably under-recognized in daily practice [6]. Interestingly, the number of organs involved did not correlate with serum tryptase levels [6].…”
Section: Clinical Classification Of Urticariamentioning
confidence: 99%
“…A recent study reported a high frequency of systemic signs and symptoms such as joint pain or swelling (55.3%), headache/fatigue (47.6%), flushing (42.7%), wheezing or breathlessness (30.1%), gastrointestinal complaints (26.2%), and palpitations (9.7%) in two thirds of adult patients with CSU that are probably under-recognized in daily practice [6]. Interestingly, the number of organs involved did not correlate with serum tryptase levels [6].…”
Section: Clinical Classification Of Urticariamentioning
confidence: 99%
“…It is thought that IL-1 plays a major role in the pathogenesis of Schnitzler’s syndrome largely due to the observation that IL-1 receptor antagonists can induce symptom remission in patients who have failed other immunomodulatory regimens 3 18 19. Moreover, the pathogenesis is thought to be mast-cell independent.…”
Section: Discussionmentioning
confidence: 99%
“…CSU is a common condition with a point prevalence of 0.5%–1% and is clinically diagnosed based on the presence of recurrent pruritic, migratory, raised, non-scarring, erythematous plaques 2. Laboratory investigations are normal, and lesions are responsive to standard CSU therapy 3. CSU is a benign and self-limiting disease lasting between 2 and 5 years 1.…”
Section: Introductionmentioning
confidence: 99%
“…Additional study of tryptase expression and function in these patients may yield important insights into the effects of specific tryptase isoforms on mast cell-mediated reactions and cellular homeostasis. Importantly, the majority of BST elevations, present in 4–6% of the general population ( Gonzalez-Quintela et al, 2010 ; Fellinger et al, 2014 ), appears to be attributable to increased TPSAB1 copy number, suggesting that this genetic trait may commonly contribute to some of the clinical phenotypes initially reported, as well as to others clinically associated with elevated BST ( Kucharewicz et al, 2007 ; Fellinger et al, 2014 ; Sahiner et al, 2014 ; Doong et al, 2017 ; Valent et al, 2017 ).…”
Section: Mast Cell Deregulationmentioning
confidence: 99%